Evaluation of the advanced yield trial on tropical wheat (Triticum aestivum) mutant lines using selection index and multivariate analysis - MUH FADLI; MUH FARID; AMIR YASSI; NASARUDDIN NASARUDDIN; MUHAMMAD FUAD ANSHORI; AMIN NUR; SURATMAN SURATMAN (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fadli M, Farid M, Yassi A, Nasaruddin, Anshori MF, Nur A, Suratman. 2021. Evaluation of the advanced yield trial on tropical wheat (Triticum aestivum) mutant lines using selection index and multivariate analysis. Biodiversitas 23: 540-547. The development of adaptive wheat (Triticum aestivum L.) mutant lines in tropical climate is a long-term solution. The advanced yield trial is an important stage in this development, which is carried out using a selection index and multivariate analysis. This study aims to determine the selection effectiveness of tropical wheat mutant lines by using a selection index and multivariate analysis. the study was conducted in three locations, which included two locations for the follow-up yield test in Kelara Village and Ujung Bulu Village (South Sulawesi, Indonesia), and the third location for the selection validation in Padang Magek Village (West Sumatra, Indonesia). This study was designed by a nested Randomized Complete Block Design (RCBD), with replications nested in locations. The samples included 16 wheat genotypes (13 mutant lines and three comparison varieties) that were replicated three times. The result showed that the selection of tropical wheat mutant lines using selection index and multivariate analysis were considered effectively with high determination value of 0.57 (57%). The results of the selection index show that seven lines were recommended for multi-location trials since they had a better selection index potential than Dewata variety.